2022
DOI: 10.1186/s12888-022-03894-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gaming disorder and its effect on anxiety and insomnia in Chinese ethnic minority adolescents

Abstract: Background The growing popularity and frequency of online game use have resulted in a large number of studies reporting various mental problems associated with game abuse in adolescents. In this article, we examined the prevalence of gaming disorder (GD) and explored the associations of GD with anxiety and insomnia symptoms in minority youth in China. Methods A total of 1494 students completed the Problematic Online Gaming Questionnaire Short-Form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…35,36 Based on the results of the questionnaire distributed, it was found that as many as 30 teenagers (78.9%) used to play cellphones/gadgets before going to bed. According to some studies, there is an effect of playing HP/gadgets 37 , seen from social media, 38 social media duration, 9,39,40,41,42 social media intensity, 43 playing games, 44,45,46 against insomnia in adolescents. Post-intervention findings showed a decrease in the insomnia scale in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Based on the results of the questionnaire distributed, it was found that as many as 30 teenagers (78.9%) used to play cellphones/gadgets before going to bed. According to some studies, there is an effect of playing HP/gadgets 37 , seen from social media, 38 social media duration, 9,39,40,41,42 social media intensity, 43 playing games, 44,45,46 against insomnia in adolescents. Post-intervention findings showed a decrease in the insomnia scale in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The total score ranges from 0 to 24, and the cut-off score for insomnia is 6 ( 48 ). According to reports, AIS has good reliability and validity in Chinese adolescent groups ( 49 , 50 ). The current sample for the AIS was calculated using Cronbach's alpha with a value of α = 0.790.…”
Section: Methodsmentioning
confidence: 99%
“…Moderate gaming is associated with relaxation and stress reduction, positively enhancing learning ability and increasing cognitive skills [5]. However, excessive gaming can lead to mental health issues such as depression and insomnia, lower academic achievement and psychosocial well-being, and lead to changes in eating habits, musculoskeletal problems, and have a negative impact on quality of life [6]. The addictive nature of internet gaming may also lead to internet gaming disorder (IGD).…”
Section: Introductionmentioning
confidence: 99%